PERAN GURU DALAM MENCEGAH KORUPSI DI SEKOLAH LUAR BIASA NEGERI KABUPATEN TOJO UNA-UNA - Sulviana A. Lumato; Mohamad Ikbal Kadir (LPPM UNiversitas Bina Mandiri Gorontalo, 2022)
This study aims to describe the role of teachers in preventing corrupt behavior and anti-corruption value learning strategies in Special Schools (SLB) in Tojo Una-una Regency. Using a descriptive qualitative approach, data were obtained through observation, in-depth interviews, and documentation of teachers and principals. The results of the study indicate that teachers have a central role as character educators, role models of moral values, and facilitators of ethical learning. The strategies implemented include concrete and visual approaches, role playing, positive reinforcement, and integration of anti-corruption values in thematic activities. The learning approach is adjusted to the individual needs of students with special needs, so that values such as honesty, responsibility, and integrity can be understood effectively. This study emphasizes the importance of synergy between teachers, principals, parents, and the environment in forming an anticorruption culture from an early age in special schools.